Chinese version of the Psychotropic-related Sexual Dysfunction Questionnaire (PRSexDQ -SALSEX): Validity and reliability for schizophrenic patients taking antipsychotics. (30th December 2016) - Wang, Yu-Xi; Zhang, Ping; Xin, Li-Min; Chen, Lin; Liu, Yan-Hong; Su, Yun-Ai; Si, Tian-Mei
Abstract: This study was designed to examine the validity and reliability of the Chinese version of the Psychotropic-Related Sexual Dysfunction Questionnaire (PRSexDQ-SALSEX) in patients with schizophrenia taking antipsychotics. It was conducted in a sample of 135 patients aged between 18 and 50 years old and diagnosed with schizophrenia. Demographic data and clinical features were assessed with PRSexDQ, the Positive and Negative Syndrome Scale (PANSS), the Clinical Global Impression (CGI), and the Udvalg for Kliniske Undersøgelser (UKU) Side Effects Rating Scale. The internal consistency of the Chinese version of PRSexDQ using Cronbach's α was 0.902. The test-retest and inter rater reliability was both high with p<0.001. PRSexDQ was correlated with corresponding items in the UKU Side Effects Rating Scale (Items 4.12–4.16), and showed good sensitivity, specificity, positive and negative predictive value. It could also clearly detect differences in SD rates of three monotherapy groups: patients treated with risperidone had the highest scores, followed by patients treated with olanzapine, whereas patients treated with aripiprazole had the lowest scores. The Chinese version of PRSexDQ is a reliable and valid instrument to assess patients with schizophrenia. Assessed by PRSexDQ, 53.2% of total subjects in our study reported symptoms of SD. Highlights: The internal consistency of the Chinese version of PRSexDQ was high. The Chinese version of PRSexDQ showed good sensitivity and specificity. SD rate among patients with schizophrenia was 53.2% assessed by PRSexDQ.